Effects of H2O2 treatment on the temperature-dependent behavior of carrier transport and the optoelectronic properties for sol–gel grown MoS2/Si nanowire/Si devices - Wu, Cheng-You; Lin, Yow-Jon; Chang, Hsing-Cheng; Chen, Ya-Hui (Journal of materials science. Materials in electronics, 2018)
The effects of H 2 O 2 treatment on the temperature-dependent behavior of carrier transport and the optoelectronic properties of a MoS 2 /Si nanowire (SiNW)/n-Si device are studied. The MoS 2 thin films are prepared using the sol–gel method. The thermionic emission–diffusion model is the dominant process in the MoS 2 /SiNW/n-Si device when there is no H 2 O 2 treatment. However, carrier transport in MoS 2 /SiNW/n-Si devices that are subject to H 2 O 2 treatment is dominated by thermionic emission, so it demonstrates reliable rectification. Passivation of the SiNW surface increases the responsivity to solar irradiation. There is a low trap density at the MoS 2 /SiNW interfaces so the increase in photocurrent density for the MoS 2 /SiNW/n-Si device that is subject to H 2 O 2 treatment is due to greater internal power conversion efficiency. The photo-response results for MoS 2 /SiNW/n-Si devices that are subject to (are not subject to) H 2 O 2 treatment confirm that the decay in the photocurrent is due to the dominance of long-lifetime (short-lifetime) charge trapping. MoS 2 /SiNW/n-Si devices that are subject to H 2 O 2 treatment exhibit reliable responsivity to solar irradiation.